Are Retail Outlets Complying with National Legislation to Protect Children from Exposure to Tobacco Displays at Point of Sale? Results from the First Compliance Study in the UK. - Douglas Eadie; Martine Stead; Anne Marie MacKintosh; Susan Murray; Catherine Best; Jamie Pearce; Catherine Tisch; Winfried van der Sluijs; Amanda Amos; Andy MacGregor; Sally Haw (PLoS ONE)
Background From April 6th 2015, all small shops in the UK were required to cover up tobacco products at point of sale (POS) to protect children from exposure. As part of a larger 5-year study to measure the impact of the legislation in Scotland, an audit was conducted to assess level and nature of compliance with the ban immediately following its introduction. Materials and methods A discreet observational audit was conducted 7-14 days post implementation which took measures of physical changes made to cover products, server/assistant practices, tobacco signage and advertising, and communication of price information. The audit was conducted in all small retail outlets (n = 83) selling tobacco in four communities in Scotland selected to represent different levels of urbanisation and social deprivation. Data were analysed descriptively. Results Compliance with the legislation was high, with 98% of shops removing tobacco from permanent display and non-compliance was restricted almost entirely to minor contraventions. The refurbishment of shops with new or adapted tobacco storage units resulted in the removal of nearly all commercial brand messages and images from POS, dropping from 51% to 4%. The majority of shops stored their tobacco in public-facing storage units (81%). Most shops also displayed at least one generic tobacco message (88%). Conclusions Compliance with Scottish prohibitions on display of tobacco products in small retail outlets was high immediately after the legislation implementation date. However, although tobacco branding is no longer visible in retail outlets, tobacco storage units with generic tobacco messages are still prominent. This points towards a need to monitor how the space vacated by tobacco products is utilised and to better understand how the continuing presence of tobacco storage units influences people's awareness and understanding of tobacco and smoking. Countries with existing POS bans and who are considering such bans should pay particular attention to regulations regarding the use of generic signage and where within the retail setting tobacco stocks can be stored.